Temperature differently affected methanogenic pathways and microbial communities in sub-Antarctic freshwater ecosystems - Lavergne, Celine; Aguilar-Munoz, Polette; Calle, Natalia; Thalasso, Frederic; Astorga España, Maria Soledad; Sepulveda-Jauregui, Armando; Martinez-Cruz, Karla; Gandois, Laure; Mansilla Muñoz, Andres Omar; Chamy, Rolando; Barret, Maialen; Cabrol, Lea (My University, 2021)
Freshwater ecosystems are responsible for an important part of the methane (CH4) emissions which are likely to change with global warming. This study aims to evaluate temperature-induced (from 5 to 20 degrees C) changes on microbial community structure and methanogenic pathways in five sub-Antarctic lake sediments from Magallanes strait to Cape Horn, Chile. We combined in situ CH4 flux measurements, CH4 production rates (MPRs), gene abundance quantification and microbial community structure analysis (metabarcoding of the 16S rRNA gene). Under unamended conditions, a temperature increase of 5 degrees C doubled MPR while microbial community structure was not affected. Stimulation of methanogenesis by methanogenic precursors as acetate and H-2/CO2 , resulted in an increase of MPRs up to 127-fold and 19-fold, respectively, as well as an enrichment of mcrAcarriers strikingly stronger under acetate amendment. At low temperatures, H-2/CO2-derived MPRs were considerably lower (down to 160-fold lower) than the acetate-derived MPRs, but the contribution of hydrogenotrophic methanogenesis increased with temperature. Temperature dependence of MPRs was significantly higher in incubations spiked with H-2/CO2, (c. 1.9 eV) compared to incubations spiked with acetate or unamended (c. 0.8 eV). Temperature was not found to shape the total microbial community structure, that rather exhibited a site-specific variability among the studied lakes. However, the methanogenic archaeal community structure was driven by amended methanogenic precursors with a dominance of Methanobacterium in H-2/CO2-based incubations and Methanosarcina in acetate-based incubations. We also suggested the importance of acetogenic H-2-production outcompeting hydrogenotrohic methanogenesis especially at low temperatures, further supported by homoacetogen proportion in the microcosm communities. The combination of in situ-, and laboratory-based measurements and molecular approaches indicates that the hydrogenotrophic pathway may become more important with increasing temperatures than the acetoclastic pathway. In a continuously warming environment driven by climate change, such issues are crucial and may receive more attention.
Keywords: 16s rrna amplicons; archaea; bacteria; limnology; methane; global warming